Maulana Azad: A Life: (By S. IRFAN HABIB) (American Journal of Islam and Society, 2025)
Mawlana Abul Kalam Azad, a multifaceted figure, was celebrated as athinker, orator, journalist, politician, leader, and Muslim intellectual, witha deep understanding of both Islamic and contemporary knowledge. S.Irfan Habib’s Maulana Azad: A Life offers a comprehensive and freshbiographical account, exploring key moments that shaped Azad’s lifeand remain relevant today (p. 2). S. Irfan Habib (b. 1931) is a prominentIndian historian of ancient and medieval India and the former AbulKalam Azad Chair at the National Institute of Educational Planning andAdministration. The book challenges prevailing historical narratives,aiming to dismantle stereotypes about the past (p. 10). Structured thematically,it includes five chapters, along with an introduction and an epilogue.